Studi Kelimpahan Gastropoda di Bagian Timur Perairan Semarang Periode Maret – April 2012 - Budi, Dinar Ayu; Suryono, Chrisna Adhi; Ario, Raden (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Coastal environment in Eastern part of Semarang is an area that changed in ecological conditions caused by the influence of a variety of human activities such as ports activity, industries, fishing activity, and common people’s residence which causes a decrease in water quality that directly affect the presence, and abundance of gastropods in that area. Purpose of this study is to find out the abundance of gastropods in coastal water environment, Eastern part of Semarang, during periods March to April 2012. This study using the descriptive method, sample survey method, and method used in determining station is purposive sampling method. Sample collected are including water quality measurement, sediments, and samples of biota that is gastropods. Sample of gastropods taken by using the dredge, by width 138cm, height 137cm, and net 500 cm long. Samples of gastropods founded then identified in Marine Biological Laboratory, Marine Faculty, Diponegoro University. Water quality measurement including physical factors, are : depth, water brightness, temperature, substrate, and chemical factors, they are : salinity, acidity (pH), dissolved oxygen (DO), and organic content. There are 14 spesies founded, they are : Architectonica perdix, Busycon canaliculatum, Conus tenuistriatus, Engina zonalis, Fasciolaria salma, Murex trapa, Nassarius javanus, N. pullus, Natica lineata, N. tigrina, Pseudoeptunea varicose, Terebralia palustris, Trigonostoma scalariformis, and Turricula javana. Highest abundance is on station II (183,67), and the lowest abundance is station VII (2,67).